Complement-Mediated Macrophage Polarization in Perivascular Adipose Tissue Contributes to Vascular Injury in Deoxycorticosterone Acetate–Salt Mice. Issue 3 (March 2015) - Ruan, Cheng-Chao; Ge, Qian; Li, Yan; Li, Xiao-Dong; Chen, Dong-Rui; Ji, Kai-Da; Wu, Yong-Jie; Sheng, Li-Juan; Yan, Chen; Zhu, Ding-Liang; Gao, Ping-Jin
<x xml:space="preserve">Abstract</x> Objective— We have previously shown an increased expression of complement 3 (C3) in the perivascular adipose tissue (PVAT) in the deoxycorticosterone acetate (DOCA)–salt hypertensive model. This study aims to examine the role and underlying mechanism of C3 in PVAT for understanding the pathogenesis of hypertensive vascular remodeling further. Approach and Results— The role of C3 in macrophage polarization was investigated using peritoneal macrophages from wild-type and C3-deficient (C3KO) mice because we found that C3 was primarily expressed in macrophages in PVAT of blood vessels from DOCA-salt mice, and results showed a decreased expression of M1 phenotypic marker in contrast to an increased level of M2 marker in the C3KO macrophages. Bone marrow transplantation studies further showed in vivo that DOCA-salt recipient mice had fewer M1 but more M2 macrophages in PVAT when the donor bone marrows were from C3KO compared with those from wild-type mice. Of note, this macrophage polarization shift was accompanied with an ameliorated vascular injury. Furthermore, we identified the complement 5a (C5a) as the major C3 activation product that was involved in macrophage polarization and DOCA-salt–induced vascular injury. Consistently, in vivo depletion of macrophages prevented the induction of C3 and C5a in PVAT, and ameliorated hypertensive vascular injury as well. Conclusions— The presence and activation of bone marrow–derived macrophages in PVAT are crucial for complement activation in hypertensive vascular inflammation, and C5a plays a critical role in DOCA-salt–induced vascular injury by stimulating macrophage polarization toward a proinflammatory M1 phenotype in PVAT.